Pengaruh Struktur Kepemilikan dan Intensitas Modal terhadap Penghindaran Pajak - Afriani, Widia; Taqwa, Salma (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to determine the effect of ownership structure and capital intensity on tax avoidance. The population used in this study are mining companies listed on the Indonesia Stock Exchange in 2021-2023. The sampling technique using purposive sampling technique, there are 44 companies used as research samples for 3 (three) years of observation with a total of 132 samples. The data used is secondary data obtained from the financial statements of mining companies listed on the Indonesia Stock Exchange. The analysis model used is panel data regression using SPSS 30 software. Based on the results of partial statistical testing, it shows that the research variables have different results. The managerial ownership variable has a significant negative effect on tax avoidance. The institutional ownership variable has no effect on tax avoidance. The foreign ownership variable has no effect on tax avoidance. The capital intensity variable has a significant positive effect on tax avoidance. For further research, other independent variables can be added, adding a research time span so that it will provide better results.